The evolution of mafic and ultramafic rocks of the Mesoproterozoic Fraser Zone, Albany-Fraser Orogen, and implications for the Ni-Cu sulphide potential of the region - Maier, W.; Smithies, R.; Spaggiari, C.; Barnes, S.; Kirkland, Chris; Kiddie, O.; Roberts, M. (2016)
The Albany–Fraser Orogen is located along the southern and southeastern margins of the Archean Yilgarn Craton and formed from at least c. 1810 to 1140 Ma during reworking of the craton, accompanied by variable additions of juvenile mantle material. The Fraser Zone is an approximately 425 km long and 50 km wide, geophysically and structurally distinct zone within the orogen, hosting abundant intrusions of predominantly c. 1305 to 1290 Ma metagabbroic rocks emplaced into sedimentary rocks belonging to the Snowys Dam Formation of the Arid Basin. Magma emplacement was most likely in a dominantly extensional setting and possibly related to orogenic collapse. The primary mafic magma had ~8.8% MgO and was derived from a depleted mantle source. This magma was contaminated with small (<<10%) amounts of crust before and during ascent and emplacement. The Fraser Zone has been the focus of considerable exploration for Ni–Cu sulfides following the discovery of the Nova–Bollinger deposit in 2012–13 in an intrusion consisting of interlayered olivine gabbronoritic, noritic, and peridotitic cumulates. Disseminated sulfides in drillcore intersecting the structurally upper portion of the intrusion, above the main ore zone, have tenors of approximately 4–5% Ni, 1–4% Cu and very low PGE concentrations (<100 ppb), consistent with derivation from magma with broadly the same composition as the regional Fraser Zone metagabbros. However, mineral chemistry suggests that the Nova–Bollinger rocks crystallized from slightly more primitive parental melts, with higher Sr (38–52) and more variable 34S (–2 to +4) than the regional metagabbros ( Sr 17–32, 34S around 0), which is consistent with the geochemical evidence for enhanced crustal assimilation of the metasedimentary country rock in a relatively large magma staging chamber. Our data identify several factors potentially critical in determining whether or not Fraser Zone mafic magmas are mineralized. These data relate to intrusion history and local geodynamic conditions. Favourable sets of factors include initial emplacement of large magma chambers within the Arid Basin, assimilation of sulfur-rich metasedimentary rock, convective compositional homogenization and sulfur-saturation prior to olivine fractionation, and tectonically induced final transport and emplacement processes which modified or sorted both silicate and sulfide minerals and drained them of liquid. Unfavourable factors include initial emplacement beneath the base of the Arid Basin, early olivine fractionation, later emplacement within the Fraser Zone as small chambers that were unable to assimilate significant volumes of country rock or to convectively homogenize subsequent hybridized magma, and final emplacement during relative tectonic quiescence. Early olivine fractionation is monitored by whole-rock and mineral Mg#, effective contamination by Arid Basin metasedimentary rocks is monitored by sulfur and Sr isotopic composition, the stage of sulfur-saturation is monitored by Ni concentration of olivine, and the intensity of tectonic activity is monitored by textural features of the cumulate rocks including the ratio of cumulate minerals to liquid. Cumulate rocks with high whole-rock and olivine Mg#, Ni-depleted olivine, crustal sulfur and Sr isotopic compositions, and extremely low concentrations of strongly incompatible trace elements reflecting cumulates with very little interstitial liquid, would all be considered indicative of high Ni–Cu sulfide prospectivity within the Fraser Zone.